Distribution of nitric oxide synthase in stomach myenteric plexus of rats - Peng, Xi (World J Gastroenterol, 2001)
AIM: To study the distribution of nitric oxide synthase (NOS) in rat stomach myenteric plexus. METHODS: The distribution of NOS in gastric wall was studied in quantity and location by the NADPH-diaphorase (NDP) histochemical staining method and whole mount preparation technique. RESULTS: NOS was distributed in whole stomach wall, most of them were located in myenteric plexus, and distributed in submucosal plexus. The shape of NOS positive neurons was basically similar, most of them being round and oval in shape. But their density, size and staining intensity varied greatly in the different parts of stomach. The density was 62 ± 38 cells/mm(2) (antrum), 43 ± 32 cells/mm(2) (body), and 32 ± 28 cells/mm(2) (fundus), respectively. The size and staining intensity of NOS positive neurons in the fundus were basically the same, the neurons being large and dark stained, while they were obviously different in antrum. In the body of the stomach, the NOS positive neurons were in an intermediate state from fundus to antrum. There were some beadlike structures which were strung together by NOS positive varicosities in nerve fibers, some were closely adherent to the outer walls of blood vessels. CONCLUSION: Nitric oxide might be involved in the modulation of motility, secretion and blood circulation of the stomach, and the significant difference of NOS positive neurons in different parts of stomach myenteric plexus may be related to the physiologic function of stomach.